ANÁLISIS CLADÍSTICO DE S1MULIUM (PTERNASPATHA) ENDERLEIN CON DATOS SOBRE SU DISTRIBUCIÓN GEOGRÁFICA (DIPTERA: SIMULIIDAE) - Coscarón, S.; Coscaron-Arias, C . L. (Acta Entomológica Chilena, 2022)
Simulium (Pternaspatha) is a peculiar Southern South American blackfly subgenus, with 26 species distributed along the Andes from Tierra del Fuego to SW Perú, and one species in Ecuador, It is a monophyletic taxon defined by two synapomorphies: 1) “female scutum gray, with 1 + I sublateral and median black, dusted, longitudinal stripes, median stripe divided longitudinally by a fine grayish line and abdomen with 1 + 1 whitish submedian spots with variable size and distribution among tergites”, and 2) “distimere of male genitalia subquadrate with slow concavity distally and subapical spine”, and without resemblance with the remaining tropical Sim ulium subgenera. A cladistic analysis was conducted using 24 morphological characters from the male, female, pupa, and larva. Polarity of characteres was based on the outgroup comparison method, using “blancasi” group, from Chile and the Peruvian desert. With mh* option of Hennig86 program 12 most parsimonious cladograms were obtained, each with 44 steps and a consistency Índex of 0,97 and retention inder of 0,98; with bb* option 86 most parsimonious trees were obtained. A strict consensus tree was calculated. This cladogram define two monophyletic groups that corresponded to “nemorale” and “nigristrigatum” groups in accordance to Coscaron and Wygodzinsky (1972). Two maps with 5. (Pternaspatha) geographical distribution and relationships of ciados with biogeographical areas are added.